Eksistensi Obligasi Syariah (Sukuk) Korporasi di Indonesia pada Masa Pandemi - Imroatus Sholiha; Nani Hanifah (Program Pascasarjana Universitas Ibrahimy, 2021)
This article explained how the existence of corporate sharia bonds (Sukuk) during the pandemic. Sukuk was one of the instruments owned by Islamic financial institutions, namely the Islamic capital market. The existence of the coronavirus had existed for one year. By using the library research method, and using qualitative descriptive, namely the method by describing and interpreting the existence of Islamic bonds (Sukuk) in the pandemic period qualitatively, namely the description and description in words based on library data, journal articles, OJK and related data. The data collection method used the documentation method then the data was processed so that it completes this article. The results showed that the record was the outstanding value of Sukuk from 2016 to January 2021 had increased from 11.88 trillion to 30.25 trillion. Meanwhile, the number of outstanding Sukuk had experienced a good development from 2016-January 2021, namely from 53 to 161. And the accumulated value of Sukuk issuance had also increased, from 2016-January 2021 from 20.43 trillion to 55.15 trillion. Meanwhile, the accumulated number of Sukuk issuances also increased from 102 to 274.